BUILDING COMMUNITY THROUGH LOCAL DRAMA ACTIVITIES IN THE CLASSROOM - Syukri, Muhammad; Mytra, Prima; Amin, Fatimah Hidayahni (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
Using a local history approach as an embedded medium can increase student engagement and achieve the goals of the learning process. The purpose of this study was to find out how to build student community through local historical drama in drama class activities. This study uses mixed methods, with observation and questionnaires as data collection instruments. Using a purposive sampling technique, 75 students were selected as a sample from a population of 3,225. Data were analyzed by Quant-Qual and interpreted by descriptive accounting. The results showed that there were no students who commented badly about the use of techniques in local historical dramas. Researchers recommend using this approach in the learning process, especially in learning English and how to build student’s community. Abstrak: Menggunakan pendekatan sejarah lokal sebagai media yang melekat dapat meningkatkan keterlibatan siswa dan mencapai tujuan dari proses pembelajaran. Tujuan penelitian ini adalah untuk mengetahui bagaimana membangun komunitas siswa melalui drama sejarah lokal dalam kegiatan drama kelas. Penelitian ini menggunakan metode campuran, dengan observasi dan kuesioner sebagai instrumen pengumpulan data. Dengan menggunakan teknik purposive sampling, dipilih 75 siswa sebagai sampel dari populasi sejumlah 3.225. Data dianalisis dengan Quant-Qual dan diinterpretasikan dengan akuntansi deskriptif. Hasil penelitian menunjukkan bahwa tidak ada satupun siswa yang berkomentar buruk tentang penggunaan teknik dalam drama sejarah lokal. Peneliti merekomendasikan penggunaan pendekatan ini dalam proses pembelajaran, khususnya dalam pembelajaran bahasa Inggris dan bagaimana membangun komunitas siswa.